2022
DOI: 10.1136/bmjopen-2021-058746
|View full text |Cite
|
Sign up to set email alerts
|

Do private providers give patients what they demand, even if it is inappropriate? A randomised study using unannounced standardised patients in Kenya

Abstract: IntroductionLow and varied quality of care has been demonstrated for childhood illnesses in low-income and middle-income countries. Some quality improvement strategies focus on increasing patient engagement; however, evidence suggests that patients demanding medicines can favour the selection of resistant microbial strains in the individual and the community if drugs are inappropriately used. This study examines the effects on quality of care when patients demand different types of inappropriate medicines.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…NA, not applicable. role in inappropriate antibiotic prescribing in those countries (30,31). Our work extends this literature, showing that inappropriate prescribing could also be driven by providers' perceptions of patient preferences (e.g., that they do not want ORS) rather than patients' expressed preferences.…”
Section: Study Contributions and Policy Implicationssupporting
confidence: 58%
See 1 more Smart Citation
“…NA, not applicable. role in inappropriate antibiotic prescribing in those countries (30,31). Our work extends this literature, showing that inappropriate prescribing could also be driven by providers' perceptions of patient preferences (e.g., that they do not want ORS) rather than patients' expressed preferences.…”
Section: Study Contributions and Policy Implicationssupporting
confidence: 58%
“…However, Lagarde and Blaauw, who also used variation in SP profiles, showed that financial incentives are not important for inappropriate antibiotic prescribing in South Africa and that providers overprescribe antibiotics even when they bear the cost of the drugs ( 29 ). Moreover, studies from Kenya and Tanzania have shown that patient preferences for antibiotics play a limited role in inappropriate antibiotic prescribing in those countries ( 30 , 31 ). Our work extends this literature, showing that inappropriate prescribing could also be driven by providers’ perceptions of patient preferences (e.g., that they do not want ORS) rather than patients’ expressed preferences.…”
Section: Discussionmentioning
confidence: 99%
“…To address these methodological issues, researchers have recently used standardised 'mystery' patients-healthy individuals sent to providers to portray specific symptoms-and shown high levels of overprovision of antibiotics. [24][25][26][27][28][29] In this paper, we build on this recent literature to answer three questions. First, we overcome empirical challenges to obtain objective and reliable measures of antibiotic overprescription for viral respiratory illnesses in South Africa, a country that has some of the world's highest rates of antibiotic resistance from both Gram-positive and Gram-negative bacteria.…”
Section: Bmj Global Healthmentioning
confidence: 99%
“…This is a particularly relevant concern in comparative studies of the public and private sectors. To address these methodological issues, researchers have recently used standardised ‘mystery’ patients—healthy individuals sent to providers to portray specific symptoms—and shown high levels of overprovision of antibiotics 24–29…”
Section: Introductionmentioning
confidence: 99%
“…The impact of AHME on management and care delivery is forthcoming (Contreras-Loya et al, 2022). AHME has also been evaluated using qualitative methods (Montagu et al, 2020;Suchman et al, 2019), and the SP data from the impact evaluation has been used to understand the impact of clients demanding different medications (Kwan et al, 2022). Here, we focus on the effects of AHME on healthcare equity.…”
Section: Introductionmentioning
confidence: 99%